Numerical analysis of the effect of electrode spacing on deposition rate profiles in a capacitively coupled plasma reactor. (5th October 2016) - Kim, Ho Jun; Lee, Hae June
Abstract: The effect of reactor dimension on deposition rate profiles is analyzed with a two-dimensional (2D) fluid simulation of a capacitively coupled plasma (CCP) reactor to deposit a hydrogenated silicon nitride (SiN x H y ) film with a SiH4 /NH3 /N2 /He gas mixture. We focus on the complex function of electrode spacing to reveal the physical relation between reactor geometry and deposition rate profiles. The simulation demonstrates that the localization of electron density is concentrated close to the powered electrode periphery for electrode spacing of 9 mm. However, the plasma distribution becomes bulk dominated with electrode spacing of 15 mm by relaxing the localization. As a result, the increase in the electrode spacing creates a more uniform electron power density profile, and the deposition rate profile of SiN x H y film changes from convex to concave in a radial direction. The change in the deposition rate profile is validated through comparison with the experimental observation, which agrees well with the simulation results with errors of less than 5%. The deposition rate profile with electrode spacing of 9 mm is very sensitive to the non-uniform gas density condition applied to the showerhead inlet. However, the deposition rate profile with electrode spacing of 15 mm is not sensitive to the inlet gas profile because of the increasing residence time. The increase of the electrode spacing promotes molecule–molecule gas phase reactions and consequently weakens the effect of the inlet boundary condition.